Identification of a determinant within the human immunodeficiency virus 1 surface envelope glycoprotein critical for productive infection of primary monocytes. - Westervelt, P (1991)
Profound differences exist in the replicative capacities of various human immunodeficiency virus 1 isolates in primary human monocytes. To investigate the molecular basis for these differences, recombinant full-length clones were constructed by reciprocal DNA fragment exchange between a molecular clone derived from a monocyte-tropic isolate (ADA) and portions of two full-length clones incapable of infection or replication in primary monocyte cultures (HXB2 and NL4-3). Virions derived from proviral clones that contained ADA sequences encoding vpu and the N and C termini of the surface envelope glycoprotein (gp120) were incapable of replication in monocytes. However, a 283-base-pair ADA sequence encoding amino acids 240-333 of the mature gp120 protein conferred the capacity for high-level virus replication in primary monocytes. The predicted amino acid sequence of this ADA clone differed from NL4-3 and HXB2 at 22 of 94 residues in this portion of gp120, which includes the entire third variable domain. Only 2 of 11 residues implicated in CD4 binding are located in this region of gp120 and are identical in HXB2, NL4-3, and ADA. Alignment of the ADA sequence with published amino acid sequences of three additional monocyte-replicative and three monocyte-nonreplicative clones indicates 6 discrete residues with potential involvement in conferring productive human immunodeficiency virus 1 infection of primary monocytes.